The Gap between Architecture Education and Architectural Profession in Iran - Hejazi, Saba (Journal of Architectural Research and Education, 2020)
Many graduates of architecture attracted to the job market find a profound gap between what they have learned in college and what is being done in their career in Iran. The educational problems that make architecture graduates inefficient in the job market are identified. Then solutions are offered to reduce the gap. Four types of questionnaires were distributed to the last year undergraduate students, professors of architecture schools and professional architects and their answers and suggestions were collected. The results show that there are some solutions for bringing architecture education closer to architectural profession: 1. participatory education, 2. establishment of non-governmental organisations, 3. linking faculties of architecture with architectural offices, and 4. revision of undergraduate curriculum of architecture.